Illicit natural resource exploitation by private corporate interests in Africa's Maritime Zones during armed conflict - Tsabora, James (School of Law, 2021)
In periods of war, African states experience great difficulty in defending maritime zones from criminality because the legal and institutional infrastructure, which guarantees the safety and security of the zones, is often highly compromised. Major maritime commercial corporate interests are exploiting economic opportunities that arise in these compromised coastal states due to war. Some of the most common exploitations of marine resources are illicit fishing, extraction of minerals, and illegal dumping of toxic substances in the territorial waters of maritime states. Such unlawful exploitation is detrimental to Africa’s economic integrity and well-being. Corporate accountability for these criminal activities would guarantee a measure of economic integrity and secure a state’s economic welfare. Increasing evidence of illicit exploitation in maritime states during periods of conflict necessarily calls for the elaboration of the rights and responsibilities of private maritime corporations in foreign waters under the United Nations Convention of the Law of the Sea, and further highlights a great need for international criminal penalties for such exploitation. This article investigates whether the relevant international legal and institutional frameworks can be relied upon to prevent illegal natural resource exploitation of Africa’s maritime zones during periods of armed conflict, and proposes a strategy for criminal sanctions against this conduct.